PERAN GURU PEMBELAJARAN AKIDAH AKHLAK DALAM MENGEMBANGKAN KECERDASAN EMOSIONAL DAN SPIRITUAL SISWA DI MADRASAH ALIYAH AL MUBALLIGHIN MUARA BUNGO - Intan Muntia; Amirul Mukminin Anwari; Edy Kusnadi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to describe and analyze the role of Islamic Theology and Ethics(Akidah Akhlak) teachers in developing students’ emotional and spiritual intelligenceat Madrasah Aliyah Al Muballighin Muara Bungo. The background of this researchis based on the importance of maintaining a balance between emotional andspiritual intelligence in education. Although students receive formal religiousinstruction, there are still many who struggle to manage their emotions properly andhave not yet demonstrated a high level of spiritual awareness. This conditionemphasizes the need for an active role of teachers in instilling emotional andspiritual values more deeply.This research employed a qualitative approach withdata collected through observation, in-depth interviews, and documentation. Theinformants consisted of the principal, Akidah Akhlak teachers, and students. Datawere analyzed using an interactive model that included data reduction, datapresentation, and conclusion drawing.The findings indicate that students’ emotionaland spiritual intelligence have not yet developed optimally. The challenges identifiedinclude: the lack of implementation of spiritual values in daily life, limited variation in teaching methods, the presence of students with inappropriate behavior, low self-confidence, academic achievement pressures, and limited instructional time. To address these challenges, Akidah Akhlak teachers have taken several efforts, suchas teaching moral values, creating engaging learning environments, providing rolemodels, offering guidance and advice, and involving other parties in studentdevelopment.